Nutritious digital menu system for Malaysian religious primary school children: improving good memories / Azila M. Sudin, Suliadi Firdaus Sufahani and Mohd Asrul Affendi Abdullah - M. Sudin, Azila; Sufahani, Suliadi Firdaus; Abdullah, Mohd Asrul Affendi (2021)
Religious (Tahfiz) school students aged 7-12 need to eat nutritious meals which contain proper calories and nutrients for appropriate development with a specific end goal to repair and upkeep the body tissues. It averts undesired diseases and contamination. Serving healthier food is a noteworthy stride towards accomplishing that goal. However, arranging a nutritious and balanced menu manually is convoluted, wasteful and tedious. The aim of this study is to develop a mathematical model with an optimization technique for menu scheduling that fulfill the whole supplement prerequisite for tahfiz school students, reduce processing time, minimize the budget and serve an assortment type of food each day. It additionally gives the flexibility for the cook to choose any food to be considered in the beginning of the process and change any favored menu even after the ideal arrangement and optimal solution has been obtained. This is called sensitivity analysis. A recalculation procedure will be performed in light of the ideal arrangement and seven days menu. The data was gathered from the Malaysian Ministry and schools’ authorities. Menu arranging is a known optimization problem. Therefore, Binary Programming alongside optimization techniques and “Sufahani-Ismail Algorithm” were utilized to take care of this issue and at the same time improving good memories for the children.